Counterinsurgency, security forces, and the identification problem distinguishing friend from foe - Magruder, Daniel L. (Studies in insurgency, counterinsurgency and national security, 2018)
This book presents a theory and empirical evidence for how security forces can identify militant suspects during counterinsurgency operations. For military practitioners, the work illustrates the critical precursor to establishing "security" during counterinsurgency operations. The book also examines the role and limits of modern technology in solving the identification problem.